Nursing theorists and their work - 4 0 16; 1943- Marriner-Tomey, Ann,;Alligood, Martha Raile; 5 (St. Louis, Missouri : Mosby, 2002)
Nursing Theorists and Their Work is the most comprehensive book on nursing theory available. This modern classic offers authoritative and up-to-date descriptions and analyses of 28 nursing theories in a clear, concise, and consistent format--back cover.
Ch. 1. Introduction to nursing theory: history, terminology, and analysis -- Ch. 2. Significance of theory for nursing as a discipline and profession -- Ch. 3. History and philosophy of science -- Ch. 4. Logical reasoning -- Ch. 5. Theory development process -- Ch. 6. Florence Nightingale: Modern nursing -- Ch. 7. Ernestine Wiedenbach: The Helping art of clinical nursing -- Ch. 8. Virginia Henderson: Definition of nursing -- Ch. 9. Faye Glenn Abdellah: Twenty-one nursing problems -- Ch. 10. Lydia E. Hall: Core, care, and cure model -- Ch. 11. Jean Watson: Philosophy and science of caring -- Ch. 12. Patricia Benner: From novice to expert: excellence and power in clinical nursing practice -- Ch. 13. Dorothea E. Orem: Self-care deficit theory of nursing -- Ch. 14. Myra Estrin Levine: The Conservation model -- Ch. 15. Martha E. Rogers: Unitary human beings -- Ch. 16. Dorothy E. Johnson: behavioral system model -- Ch. 17. Sister Callista Roy: Adaptation model -- Ch. 18. Betty Neuman: Systems model -- Ch. 19. Imogene King: Interacting systems framework and theory of goal attainment -- Ch. 20. Nancy Roper, Winifred W. Logan, and Alison J. Tierney: The Elements of nursing: a model for nursing based on a model of living -- Ch. 21. Hildegard E. Peplau: Psychodynamic nursing -- Ch. 22. Ida Jean Orlando (Pelletier): Nursing process theory -- Ch. 23. Joyce Travelbee: Human-to-human relationship model -- Ch. 24. Katharine Kolcaba: Theory of comfort -- Ch. 25. Helen C. Erickson, Evelyn M. Tomlin, and Mary Ann P. Swain: Modeling and role-modeling -- Ch. 26. Ramona T. Mercer: Maternal role attainment -- Ch. 27. Kathryn E. Barnard: Parent-child interaction model -- Ch. 28. Madeleine Leininger: Culture care: diversity and universality theory -- Ch. 29. Rosemarie Rizzo Parse: Human becoming -- Ch. 30. Merle Mishel: Uncertainty in illness -- Ch. 31. Margaret A. Newman: Model of health -- Ch. 32. Evelyn Adam: Conceptual model for nursing -- Ch. 33. Nola J. Pender: The Health promotion model -- Ch. 34. State of the art and science of nursing theory.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Philosophy. -- Nursing;Nursing models.;Nursing Theory;Nurses -- 20 -- Biography.;Biography.; 20; 2